2022
DOI: 10.1038/s41467-022-30127-8
|View full text |Cite
|
Sign up to set email alerts
|

Free charge photogeneration in a single component high photovoltaic efficiency organic semiconductor

Abstract: Organic photovoltaics (OPVs) promise cheap and flexible solar energy. Whereas light generates free charges in silicon photovoltaics, excitons are normally formed in organic semiconductors due to their low dielectric constants, and require molecular heterojunctions to split into charges. Recent record efficiency OPVs utilise the small molecule, Y6, and its analogues, which – unlike previous organic semiconductors – have low band-gaps and high dielectric constants. We show that, in Y6 films, these factors lead t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
233
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(249 citation statements)
references
References 75 publications
13
233
3
Order By: Relevance
“…7,10,34 This low EQE is likely due to the single-component nature of the NPs, in which there is a lower driving force for charge separation when compared to a donor:acceptor heterojunction. In Y6 films, most excited states are lost within ∼100 ps of excitation,, 24,27,35 indicating that the formation and persistence of free charges may be limited by exciton-exciton and charge recombination in the NP bulk. Y6 NPs have similarly short excited-state lifetimes, which are further discussed later in this article.…”
Section: Photocatalytic Hydrogen Evolutionmentioning
confidence: 99%
See 4 more Smart Citations
“…7,10,34 This low EQE is likely due to the single-component nature of the NPs, in which there is a lower driving force for charge separation when compared to a donor:acceptor heterojunction. In Y6 films, most excited states are lost within ∼100 ps of excitation,, 24,27,35 indicating that the formation and persistence of free charges may be limited by exciton-exciton and charge recombination in the NP bulk. Y6 NPs have similarly short excited-state lifetimes, which are further discussed later in this article.…”
Section: Photocatalytic Hydrogen Evolutionmentioning
confidence: 99%
“…To understand the reason for such a significant difference in H 2 evolution between Y6 NPs stabilized by TEBS and SDS, we considered how Y6 NPs are able to evolve H 2 . Studies of Y6, both on its own and in donor:Y6 blends, have suggested that the unique packing of the material allows Y6 excitons to partially 24 or fully 26,27 separate into free charges within Y6 domains, as well as at donor-Y6 interfacial sites. During photocatalysis, the generation of separated charges should allow the material to form surface deposits of Pt, through reduction of Pt cations by free electrons at the surface of the NP.…”
Section: Photocatalytic Hydrogen Evolutionmentioning
confidence: 99%
See 3 more Smart Citations